Correlation between change in serum creatinine concentration and renal cortical anisotropic backscattering artifact in azotemic cats during hospitalization - Ming-Jen Kang; Pin-Chen Liu; Hock Gan Heng; Kuan-Sheng Chen (Veterinary Quarterly, 2024)
Information on the clinical outcomes of feline azotemia using ultrasound examinations is limited. This study aimed to understand the correlation between cortical anisotropy backscattering artifact (CABA) and serum creatinine (sCr) changes in feline azotemia after hospitalization and to investigate whether CABA is useful for predicting the clinical outcome of feline azotemia. Sixty-five hospitalized cats with azotemia, including 49 cats with moderate or severe azotemia (severe group) and 16 cats with mild azotemia (mild group). This retrospective study reviewed the CABA using ultrasound images of cats hospitalized with azotemia between 2016 and 2021. The correlation between CABA and the clinical outcomes of cats with azotemia was investigated using the chi-squared or Fisher’s exact test, and the intra- and inter-observer agreements in CABA were assessed using McNemar’s and Cohen’s kappa tests. The presence of CABA was significantly positively correlated with the clinical outcomes of cats with azotemia only in the severe group (p = 0.0034, odds ratio = 8.57). There was no association between CABA and clinical outcomes in cats with mild azotemia (p = 0.75). CABA can be used for clinical outcome prediction in moderate and severe feline azotemia, with a sensitivity of 80.8% and a specificity of 73.9%. Also, satisfactory intra- and inter-observer agreements were revealed in the detection of CABA during ultrasound image review. Our study demonstrated that cats with moderate and severe azotemia with CABA observed during ultrasonography might have better clinical outcomes. These findings provide additional information on the prognosis and treatment of feline azotemia.